Characterization of 1D Grating Standard for National Laboratory Comparison Using Scanning Electron Microscope - Asep Ridwan Nugraha; Ardi Rahman; Beni Adi Trisna (Instrumentasi, 2018)
Nanometrology, which is dimensional metrology on the nanometer scale, is rapidly gaining importance. In Nanometrology, length standard traceable measurements are required to certify the values obtained from measurements. Standard Reference Material (SRM) is a sample for calibrating the magnification scale of a Scanning Electron Microscope (SEM). The standard are produced by recording a precision, laser-generated, interference pattern using photosensitive materials and other processing steps. This fabrication technique provides an accurate measure of the period of the line-space. Some of the critical quality attributes of a pitch standard are (1) the fundamental pitch distance, (2) the uniformity of the pitch, (3) the quality of the line edge roughness, (4) the imaging contrast that it produces, (5) the accuracy of the certified pitch value, and (6) the traceability of the certified pitch value to an internationally recognized standard. In this paper, we describe characterization of 1D grating standard with nominal 700 nm and 300 nm using SEM and its measurement uncertainty. The measurements were performed at 10 differents measurement position at each nominal. Total number of pitch at all measurement position in each nominal was 180. An image was taken at each measurement position. The average pitch of them represents the pitch value of the specimens. The results shows measured pitch for nominal 700 nm is 700.3 nm and 300 nm is 293.6 nm with measurement uncertainty for nominal 700 nm is 5.5 nm nominal 300 nm is 4.4 nm.